Rhetorics of silence/listening and teaching trauma: Holocaust testimony in the composition classroom - Miller, Teva, author; Langstraat, Lisa, advisor; Jacobi, Tobi, committee member; Alexander, Ruth, committee member (Colorado State University. Libraries, 2010)
Many scholars and educators who have taught Holocaust testimony and literature in their classes have offered numerous pedagogical methods to outline best practices, ethical concerns, and student engagement. While some of these methodologies are particularly instructive for the first year college composition course, most do not address the gaps or silences found in Holocaust testimony. Other pedagogical methods tend to lack the affective component that is an unavoidable part of teaching trauma texts. In this thesis, I offer a heuristic that can be used in the composition classroom to engage with Holocaust testimony. I argue that there is a need for this heuristic because it not only attends to the affective economies that are vital and inseparable from reading and writing about Holocaust testimony, but also because it re-privileges silence as a powerful rhetorical act made by both survivors and secondary witnesses. It also works to destabilize and disrupt “sentimental” student responses that tend to thwart invested critical analysis and which often lead to dehumanizing depictions of victim as well as potential misappropriations of a victim’s or survivor’s words.
Covers not scanned.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Holocaust, Jewish (1939-1945) -- Study and teaching (Higher); Heuristic